2022
DOI: 10.3390/antibiotics11111528
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Characteristics of Nebulized Colistimethate Sodium Using Two Different Types of Nebulizers in Critically Ill Patients with Ventilator-Associated Respiratory Infections

Abstract: Background: Rising antimicrobial resistance has led to a revived interest in inhaled colistin treatment in the critically ill patient with ventilator-associated respiratory infection (VARI). Nebulization via vibrating mesh nebulizers (VMNs) is considered the current standard-of-care, yet the use of generic jet nebulizers (JNs) is more widespread. Few data exist on the intrapulmonary pharmacokinetics of colistin when administered through VMNs, while there is a complete paucity regarding the use of JNs. Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
(67 reference statements)
0
4
0
Order By: Relevance
“…However, its nephrotoxicity and neurotoxicity pose challenges when using colistin [ 17 , 18 ]. To address this issue, clinical studies and pharmacokinetic research have been conducted on the clinical efficacy and pharmacokinetics of CMS nebulization, either as adjunctive therapy or as an alternative to IV colistin administration [ 19 , 20 ]. Nevertheless, there is a paucity of population PK research on CMS nebulization, which is why we investigated population PK characteristics in the ELF and plasma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, its nephrotoxicity and neurotoxicity pose challenges when using colistin [ 17 , 18 ]. To address this issue, clinical studies and pharmacokinetic research have been conducted on the clinical efficacy and pharmacokinetics of CMS nebulization, either as adjunctive therapy or as an alternative to IV colistin administration [ 19 , 20 ]. Nevertheless, there is a paucity of population PK research on CMS nebulization, which is why we investigated population PK characteristics in the ELF and plasma.…”
Section: Discussionmentioning
confidence: 99%
“…Comparatively, a previous study by Kyriakoudi et al, using 2 MIU of CMS, equivalent to 160 mg of CMS sulfate or 60 mg of CBA, administered via vibrating mesh and jet nebulizers, reported median (IQR) maximum ELF concentrations of 10.4 (4.7–22.6) mg/L and 7.4 (6.2–10.3) mg/L, respectively. Plasma colistin concentrations in that study were documented as 2.6 (2.0–3.5) mg and 0.3 (0.3–1.6) mg for vibrating mesh and jet nebulizers, respectively [ 20 ]. Boisson and colleagues administered 2 MIU of CMS via aerosol and reported a wide range of ELF concentrations ranging from 9.53 to 1137 mg/L.…”
Section: Discussionmentioning
confidence: 99%
“…Although published data support the superiority of vibrating mesh over jet and ultrasonic nebulizers, mainly due to advantages related to their manufacturing characteristics, lung PK data comparing different devices are missing, while in the study of Benitez-Cano et al plasma colistin concentrations were higher with the use of vibrating-mesh compared to jet nebulizers [ 20 ]. A recent study by Kyriakoudi et al compared ELF and plasma PK data of patients with VAP receiving 2 MIU of CMS either via a vibrating mesh or a jet nebulizer [ 59 ]. The maximum colistin concentrations in ELF, obtained with a vibrating mesh nebulizer were 10.4 (4.7–22.6) mg/L, while maximum ELF colistin values obtained with a jet nebulizer were 7.4 (6.2–10.3) mg/L.…”
Section: Pharmacokinetics Of Nebulized Colistimethate Sodiummentioning
confidence: 99%
“…However, looking across studies, plasma concentrations of formed colistin present variability after nebulization of different doses of CMS and do not follow a linear increase after administration of higher doses. Studies using low doses of nebulized CMS reported higher concentrations of colistin in plasma [ 31 , 59 ] compared with studies administrating high doses of nebulized CMS, which demonstrated low plasma colistin concentrations [ 19 , 20 ]. These discrepancies may be explained either by the PK properties of the drug or by the potential hydrolysis of CMS during analytic procedures, facts that may have biased measured colistin concentrations in plasma [ 60 ].…”
Section: Pharmacokinetics Of Nebulized Colistimethate Sodiummentioning
confidence: 99%